Prevalence of feco-oral transmitted protozoan infections and associated factors among university students in Ethiopia: a cross-sectional study - Behailu Hawulte Ayele; Ayele Geleto; Desalegn Admassu Ayana; Muhedin Redi (BMC Infectious Diseases, 2019)
Abstract Background An estimated 60% of the world’s population is infected with one form of intestinal parasites. Amoebiasis and giardiasis are among the leading intestinal protozoan infections that affected mankind. However, literature that shows the magnitude of the problem among university students in Ethiopia is at scarce. Therefore, this study was aimed at assessing the prevalence of feco-oral transmitted protozoan infections and associated factors among sport festival participant universities in Ethiopia. Methods A cross-sectional study design was conducted among 483 randomly selected university sport festival participant students. A self-administered questionnaire was used to collect the data. Stool specimens were examined using direct wet mount and formol-ether concentration techniques. The data were entered into Epi Info version 6.04 and were analyzed using SPSS version 20.0 statistical software. Multivariable logistic regression analysis was done to control the possible confounders and an odds ratio with a 95% confidence interval at p < 0.05 was used to identify an association between variables. Result The overall prevalence of intestinal protozoan infections was 140(28.9%) with the predominantly higher prevalence of E. histolytica/E. dispar 95(19.7%). The female respondents were at lower risk of infections compared to their male counterparts (AOR = 0.48, 95% CI: 0.22, 0.97]. Participants with educated father (AOR = 0.62, 95% CI: 0.12, 0.86) and those who received pocket money of > 347 Ethiopian Birr (~ 14 USD) per month (AOR = 0.20, 95% CI: 0.12, 0.74) were at lower risk of infections. However, being married (AOR = 1.42, 95% CI: 1.10, 2.23), rural resident (AOR = 1.82, 95% CI: 1.21, 3.32) and university stay for two or more years (AOR = 2.21, 95%CI: 1.48, 3.87) were more likely to be infected with protozoan infections. Conclusion The prevalence of intestinal protozoan infection among students who attend higher educational institutions was very high. Infection prevention strategies should be undertaken at respective universities with special focus to senior students and students from the rural area.